Primary succession and ecosystem rehabilitation - Walker, Lawrence R. (Cambridge University Press, 2003)
The first comprehensive summary of ecological development following dramatic natural and human-induced disturbances. Ecological theory and practical management issues are linked, resulting in an important reference for researchers and professionals, and a valuable graduate text.